[Three Black students on Dexter Lawn] (1992)
One student is wearing a white shirt and giving the peace sign with their left hand. Another student in overalls is holding a drum. The third student is wearing a black shirt and shorts. A sign in an Engineering West window in the background reads 'What's the rule?'.